An endodontic practice profile amongst general dental practitioners in Kathmandu: A questionnaire survey - Shrestha, D; Dahal, M; Karki, S (Journal of College of Medical Sciences-Nepal, 2014)
Objective To investigate the endodontic practice profile of general dental practitioners. To explore the materials and methods employed by them in Kathmandu valley. To compare these findings with well acknowledged international academic standards. Methods Questionnaires with 18 closed-ended questions were distributed among randomly chosen 120 general dental practitioners of Kathmandu, working in various government or private hospital or clinics.The data were collected and descriptive statistical analysis was done. Results Out of 120 questionnaires, only 110 that were completely filled were included in the study .Most general dental practitioners (97%) regularly did multi-rooted root canal treatments and followed multivisit root canal treatment.. Radiograph with instrument in canal was used by 80% of general dental practitioners to determine the working length while only 36% used electronic apex locator which is considered to be more reliable. Half of them (57%) used nickel-titanium files for cleaning and shaping but only 23% used crown down technique. Sodium hypochlorite and calcium hydroxide was the most popular irrigation solution and intra-canal medicament respectively. Majority of general dental practitioners (91%) used lateral compaction technique for root canal obturation. Sixty three percent used zinc oxide eugenol as root canal sealer and 46% used endomethasone. They seem to overuse antibiotics in cases requiring endodontic therapy. Only 48% used autoclave for sterilization of endodontic files while 86% never used rubber dam. Eight three percent of them felt the need of further endodontic training and 42% of them preferred post-graduate dental program. Conclusion This study shows that the standard guidelines and new technologies for endodontic treatments are not implemented by many general dental practitioners of Kathmandu and require further endodontic trainings. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 40-50 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10235